Reduction of Black Carbon Emissions from Residential Wood Combustion in the Arctic. Black Carbon Inventory, Abatement Instruments and Measures. - Arctic Contaminants Action Program (ACAP) (Arctic Contaminants Action Program (ACAP), 2014)
This ACAP report on the reduction of black carbon emissions from residential wood combustion was initiated in 2010 and officially approved by ACAP WG in 2012. The project presents a description of the status in Norway, Finland, Sweden, Denmark, Canada and USA, and provides a set of recommendations for consideration. The ACAP report has been written by a team of nominated national experts with support from SINTEF and Norwegian Energy. The report does not necessarily reflect the views of individual Arctic Council countries, other ACAP members or the Arctic Council itself.